1984
DOI: 10.1159/000118859
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Brainstem Reflex Mechanisms in Relation to the Transition from Liquid to Solid Food Ingestion

Abstract: Reflex activity was induced in the digastric and other submandibular muscles of pre-weaning rats, rabbits, cats and guinea pigs by electrical stimulation of the mouth. At birth, rats, cats and rabbits had long-latency reflexes which shortened with maturation. In the rat and rabbit, adult values are reached a day or so before they are known to ingest solid food. Only the guinea pig, which eats solids on day 1, had the adult latency at birth. The time course of the latency reduction in the rabbit appeared to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Alley [1973] also demonstrated that synaptogenesis occurred on Me5 neurons between P3 and P15. Functionally, jaw muscle electromyography patterns change in accordance with the transition from suckling to chewing behaviors [Westneat and Hall, 1992], and a decrease in the latency of activation of jaw-opener motoneurons, following stimulation of the jaw-openeing reflex, is observed [Thexton and McGarrick, 1984]. We propose that changes in mGluR profiles in these neurons during early postnatal development may underlie trophic changes in trigeminal neurons as well as functional changes in jaw muscle activity patterns following reflex and central activation.…”
Section: Developmental Considerationsmentioning
confidence: 81%
“…Alley [1973] also demonstrated that synaptogenesis occurred on Me5 neurons between P3 and P15. Functionally, jaw muscle electromyography patterns change in accordance with the transition from suckling to chewing behaviors [Westneat and Hall, 1992], and a decrease in the latency of activation of jaw-opener motoneurons, following stimulation of the jaw-openeing reflex, is observed [Thexton and McGarrick, 1984]. We propose that changes in mGluR profiles in these neurons during early postnatal development may underlie trophic changes in trigeminal neurons as well as functional changes in jaw muscle activity patterns following reflex and central activation.…”
Section: Developmental Considerationsmentioning
confidence: 81%
“…The lack of consistent findings across all animals is surprising given the previous work in rats demonstrating ipsilateral loss of the jaw-opening reflex immediately following unilateral LN injury (Radwan & Thexton, 1993). The reflex is thought to be critical for regulating jaw movements during the gape cycle (Haraguchi et al, 1994;Lund, Kolta, Westberg, & Scott, 1998), and appears to mature during when animals begin to ingest solid foods (Thexton & McGarrick, 1984). The pigs used here were weaned at 3 weeks, and while not fully craniodentally mature, have reached the stage identified by (Huang, Zhang, & Herring, 1994) in which adult masticatory behavior and physiology have been acquired.…”
Section: Discussionmentioning
confidence: 93%
“…10 In the present study, this sucking-chewing transition in experimental rats that have been fed a liquid diet since the weaning time may be impeded. Therefore, the long-latency reflex, which is typically found in immature rats, 10 was recorded from adult rats in the experimental group when evoked by low-intensity electrical stimulation of the ipsilateral IAN. It may not be possible to accept totally that only afferent fibers mediating the nonnociceptive JOR were activated in this study.…”
Section: Discussionmentioning
confidence: 73%
“…9 In more detailed literature, it was found that the latency of the JOR in neonatal rats was much longer than in adults, and the short-latency digastric reflex was recommended as the necessary precondition for adult oral function. 10 Mastication is an acquired-learning function, which has the critical period for programming during young ages. 11 Normally, juvenile changes could be directed to achieve optimal masticatory function in an adult.…”
Section: Introductionmentioning
confidence: 99%